Post-sunset rise of equatorial F layer—or upwelling growth? - Tsunoda, Roland T.; Saito, Susumu; Nguyen, Trang T. (Progress in earth and planetary science, 2018)
According to the so-called upwelling paradigm, development of equatorial plasma bubbles (EPBs) involves (1) appearance of an upwelling (i.e., local uplift with a zonal width of ~ 400 km) in the bottomside of the equatorial F layer, (2) its growth via the F -region interchange instability during the post-sunset rise (PSSR) of the F layer, and (3) launching of EPBs, which starts near the end of PSSR, from within the confines of the upwelling. In this description, the PSSR is presumed to be the primary driver of the paradigm, with upwelling growth dependent on PSSR strength. As constructed, the paradigm describes EPB development when PSSR is strong (i.e., high solar activity), but not when it is weak. We, show, for the first time, that when PSSR is weak (e.g., low solar activity), upwelling growth can still be comparable in strength to what would be considered a strong PSSR, and that this growth drives EPB development. Given that EPBs do not develop outside of upwellings, regardless of solar activity, we are led to conclude, against mainstream thinking, that the controlling driver for EPB development is upwelling growth, not PSSR. For continued progress toward understanding EPB development, a crucial next step is to identify the source mechanism for upwelling growth, especially when PSSR is weak, and to better understand the complexities of the underlying physics.